Pengaruh Latihan Kaki Diabetik Menggunakan Bola Plastik terhadap Neuropati Diabetik dan Waktu Pengisian Kapiler pada Penderita Diabetes Melitus Tipe 2 di Puskesmas Mojolangu Malang - Wiyono, Joko; Pramata Putri, Diva Calista; Hidayah, Nurul; Diah Ciptaningtyas, Maria (Jurnal Kesehatan Manarang, 2025)
Complications of Type 2 DM can cause peripheral nerve disorders or diabetic neuropathy and decreased blood circulation in the legs. Managing chronic complications in people with Type 2 DM involves performing diabetic foot exercises using a plastic ball. However, using a plastic ball is rarely taught to people with diabetes. This study aims to analyze the effect of diabetic foot exercises using a plastic ball on diabetic neuropathy and capillary refill time in people with Type 2 diabetes mellitus at the Mojolangu Public Health Center in Malang. This research is a quasi-experiment with a pretest-posttest control group design and used purposive sampling with 36 respondents. Data collection was done using the DNS-score questionnaire and physical examination of CRT. Analysis was conducted using the Wilcoxon signed ranks test. The result of the Wilcoxon signed ranks test for pretest-posttest neuropathy was a p-value of 0.012 (p < 0.05) and for pretest-posttest CRT, a p-value of 0.046 (p < 0.05). The conclusion of this study is that there is an effect of diabetic foot exercises using a plastic ball on diabetic neuropathy and capillary refill time in people with Type 2 DM at the Mojolangu Public Health Center in Malang. It is hoped that health workers will provide education and support to people with DM to perform diabetic foot exercises using a plastic ball correctly and regularly to help prevent the severity of neuropathy complications.